Estágio Profissional: O culminar de desafios para ser docente - Daniela Filipa Lameirão Gonçalves (2023)
This document refers to describing some passages of what was the professional internship, carried out within the scope of the second year of the 2nd Cycle of Master's Degree in Teaching Physical Education in Basic and Secondary Education, at the Faculty of Sports of the University of Porto. The fact that the internship is included in my course creates the opportunity to get to know the world of work. This began on September 1, 2022 and ended on June 14, 2023. As the professional internship is a supervised practice, it took place at Escola Básica Pêro Vaz de Caminha, headquarters of the School Group with the same name, located in Porto. This group is located in a disadvantaged environment, therefore integrated into the Priority Intervention Educational Territories Program. For the production of this report, some chapters were created to try to demonstrate the passages of this adventure of an anxious intern student, but with an immense desire to dive into the adventure. So the first chapter concerns the Introduction; the second, is of a more personal nature, seeks to show my journey throughout life; the third is the institutional framework, which addresses the characteristics of the school, the PE group, the internship center and the cooperating teacher; the fourth, is the organization and management of teaching and learning, intends to describe the context in which the internship took place; the fifth, is the participation in the school and relations with the community, encompasses all the activities in which the intern student participates and finally, professional development, which consists of carrying out an investigation, which in this case seeks to find strategies to try to include students who were highlighted as less active during the game.